Theoretical study of N2O reduction by CO in Fe-BEA zeolite - Fischer, Gerd; Goursot, Annick; Coq, Bernard; Delahay, Gerard; Pal, Sourav (Chemphyschem, 2006)
Quantum mechanical (QM) and QM/molecular mechanics (MM) studies of the full catalytic cycle of N2O reduction by CO in Fe-BEA zeolite, that is, oxidation of BEA-Fe by NO and reduction of BEA-Fe-alpha O by CO, is presented. A large QM cluster, representing half of the channel of the BEA zeolite, is used. The contribution of the MM embedding to the calculated activation energies is found to be negligible. The minimum-energy paths for N2O decomposition and reduction with CO are calculated using the nudged elastic bond (NEB) method. Calculated band experimental activation energies ore in good agreement The two possible orientations for the gaseous molecules adsorbing on the Fe site that ore found lead to different activation energies.
Keywords: Density functional calculations; iron; nitrogen oxides; reaction mechanisms; zeolites

Theoretical study of frequency and temperature dependence of dipole-quadrupole polarizability of P-4 and adamantane - Shedge, Sapana V.; Pal, Sourav; Koester, Andreas M. (Chemical Physics Letters, 2012)
The frequency and temperature dependence of dipole-quadrupole polarizability of tetrahedral P-4 and adamantane molecules have been studied using first-principle all-electron density functional theory calculation. The recently developed time-dependent auxiliary density functional theory is extended for the calculation of dynamic dipole-quadrupole polarizabilities. Temperature effects are incorporated by Born-Oppenheimer molecular dynamics (BOMD) simulations recorded up to 100 ps. The dynamic dipole-quadrupole polarizabilities are calculated along these trajectories. The frequency and temperature effects can be significant for the accurate calculation of dipole-quadrupole polarizability. We have also identified the main reason for the observed discrepancy between experiment and theory in the case of adamantane. (c) 2012 Elsevier B.V. All rights reserved.

Transition metal doped aluminum clusters: an account of spin - Sengupta, Turbasu; Das, Susanta; Pal, Sourav (Journal of Physical Chemistry C, 2016)
The influence of spin on the properties of small sized transition metal doped aluminum clusters are investigated in the framework of density functional theory (DFT). Detailed analysis on minimum spin doped aluminum clusters has shown prominent indication of odd even oscillation in various calculated properties, supporting the presence of jellium shell structures within them. However, optimized high spin ground state counterparts, on the other hand, show rather smooth trends consistent with the properties of bulk materials. Resemblance to the bulk transition metals is further reflected in the gradual declining trends of heat of adsorption of CO2 molecule on cluster surface by sequentially changing the dopant atom from scandium to zinc. All the observations are also compared and found to be consistent with the earlier theoretical and experimental findings as obtained in the current literature. The similarities in the properties between atomic clusters and the bulk material is of utter importance and indeed precious considering the promising influence of the acquired information in understanding the process of evolution of nanoparticles from constituent atoms.